Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1210/endo.139.9.6184
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Processing and Activity of Type I Insulin-Like Growth Factor Receptor in the Furin-Deficient LoVo-C5 Cells*

Abstract: To investigate endoproteolytic processing of the type I insulin-like growth factor receptor (IGF-IR), we have examined its structure and activity in the furin-deficient LoVo-C5 cell line. Immunoprecipitation experiments using the monoclonal anti-IGF-IR antibody (alpha-IR3) showed that LoVo-C5 cells expressed a major high molecular mass receptor (200 kDa) corresponding to the unprocessed alpha/beta pro-receptor. A small amount of successfully cleaved alpha/beta heterodimers was also produced, indicating a resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…[ 125 I]IGF-I binding study using these LoVo-C5 cells showed that the affinity for IGF-I of each IGF-IR on these cells was not decreased, but the number of IGF-I binding sites on the cells was significantly lower. Therefore, these LoVo-C5 cells expressing proIGF-IR could not induce intracellular signaling such as ␤-subunit tyrosine autophosphorylation (33). These reports strongly suggest that mutation at the cleavage site of proIGF-IR, as observed in our patients, may cause failure of intracellular signaling transduction and abolish IGF-IR functions such as cell growth, transformation, and development.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…[ 125 I]IGF-I binding study using these LoVo-C5 cells showed that the affinity for IGF-I of each IGF-IR on these cells was not decreased, but the number of IGF-I binding sites on the cells was significantly lower. Therefore, these LoVo-C5 cells expressing proIGF-IR could not induce intracellular signaling such as ␤-subunit tyrosine autophosphorylation (33). These reports strongly suggest that mutation at the cleavage site of proIGF-IR, as observed in our patients, may cause failure of intracellular signaling transduction and abolish IGF-IR functions such as cell growth, transformation, and development.…”
Section: Discussionsupporting
confidence: 57%
“…Lehmann et al (33) reported that LoVo-C5 cells lacking furin, which cleaves proIGF-IR into ␣-and ␤-subunits, expressed a major high-molecular-mass proIGF-IR (200 kDa) instead of mature IGF-IR on the cell surface. [ 125 I]IGF-I binding study using these LoVo-C5 cells showed that the affinity for IGF-I of each IGF-IR on these cells was not decreased, but the number of IGF-I binding sites on the cells was significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…In these receptors, cleavage of the precursor proteins serves to generate the subunits that constitute the mature two-chain receptors and does not directly involve exposure of sites for ligand binding. Thus, the proforms of the insulin receptor, the hepatocyte growth factor receptor and the LRP are all capable of ligand binding, and major dysfunction of uncleaved receptors, as seen with the insulin-like growth factor-1 receptor, most likely results from a general malconformation (Mark et al, 1992;Sugibayashi et al, 1992;Komada et al, 1993;Willnow et al, 1996a;Lehmann et al, 1998). Thus, sortilin is the first example of furin-mediated receptor activation.…”
Section: Sortilin Is the First Example Of A Receptor Activated By Furmentioning
confidence: 99%
“…However, the expression levels of furin vary among different tissue and cell types [13,19,23] and different stages of cell differentiation [24], indicating that precise regulation of spatial and temporal expression of furin is important for development. As detailed previously, furin plays an important role in processing important factors involved in trophoblast syncytialization, including IGF-I, IGF1R [25,26] VEGF [27] and syncytins [17,18]. More importantly, deletion of the FUR gene in mice leads to early embryonic death at E10.5 due to developmental defects and failure of allantois-chorion fusion [28], a key step and a pre-requisite for trophoblast syncytialization.…”
Section: Introductionmentioning
confidence: 99%